Разлози и последице угрожености социјалног живота услед помањкања реалног етичког образовања - Донев, Дејан (Педагошки факултет, Јагодина, 2008)
The derogating of the ethical values in social life is what brought the transition, because we forgot that for the development of these societies it is to determinate how to replace one system of ethical values with other, particularly in the societies where the role of the ethics was victim of the politics and ideology. The citizens, who didn’t learn in the past system how to deal with freedom, stared abusing it. The result is exchanged places of good and bad on the scale of ethical and moral values, so everything that is functional for our survival and existence becomes valuable, and evil is everything that disturbs our comfort and stops us in fulling up the historical hunger which we compensated with the status symbols. This leads the societies in situations where the ethics in social life is wished, but not a real starting point, because we didn’t determinate the role of ethical values for social life, especially when the life is in state of victimizing by the necessities of daily-political interests instead to be a process of building of ethical value for individuals and society as a way to avoid the consequences of an untailored transition to the culture and heritage of the people. This imposes the necessity of determination of the role of ethics for social life, if we won’t finally to confine: do we have to understand the social life as a space for overrunning of the social conflicts, or we’ll still allow this space to be used for hiding the governmental manipulations of individual’s sovereignty and identity of citizens!?
Causes and consequences of endangering social life due to the shortage of true ethical education